Factors Affecting Ground Water Level In Catchment Area of Yamuna River In Haryana: Implications of Groundwater Depletion in the Yamuna River Catchment Area of Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2012)
It is an established fact that it is not feasible to meet all the waterneeds through withdrawal of groundwater as almost entire Haryana has come underdark zone.